Cascade of the acylation/intramolecular oxo-Diels–Alder reaction for the diastereoselective synthesis of thienyl substituted hexahydropyrano[3, 4-c]pyrrole-1, 6-diones. (28th April 2023) - Zaytsev, Vladimir P.; Surina, Nataliya S.; Pokazeev, Kuzma M.; Shelukho, Evgeniya R.; Yakovleva, Elizaveta D.; Nadirova, Maryana A.; Novikov, Roman A.; Khrustalev, Victor N.; Zubkov, Fedor I.
Graphical abstract: Highlights: A preparative IMODA strategy for the synthesis of pyrano[3, 4- c ]pyrrole-1, 6-diones was proposed. The reaction pathway developed is simple and strongly depends on substituents in thiophene ring. The key step proceeds under mild reaction conditions and with a high level of diastereoselectivity. Abstract: We have developed an efficient approach toward the synthesis of functionalized hexahydropyrano[3, 4- c ]pyrrole-1, 6-diones from readily accessible 3-thienylsubstituted allylamines and maleic anhydride. This transformation begins with the N -acylation of the allylamines with the anhydride, followed by the intramolecular oxo -Diels–Alder reaction (IMODA), which is accompanied by the tautomerization step, and ends with the formation of saturated pyrano[3, 4- c ]pyrroles.